Application of Formative Assessment to Analyze Students' Problem-Solving Skills - Nur Istiqlaliyah Mahardika; Abu Zainuddin (IKIP Mataram, 2022)
The purpose of this study was to investigate students' problem-solving abilities using parabolic motion material through the use of formative assessments. The research method adopted is a survey combined with a qualitative descriptive analysis. This study was conducted at SMA Muhammadiyah X Surabaya with 123 students as respondents, 65 of whom were male and 58 of whom were female. On the parabolic motion material, the question instrument is utilized to examine the profile of problem-solving abilities. The results indicated that the problem-solving skill profile of X MIPA students at SMAM X Surabaya was low, with 49.94% falling into the inadequate category. Female students have a stronger capacity for problem-solving than male students. These findings demonstrate that students each possess unique strengths and advantages. Formative assessment has a beneficial effect on students' problem-solving abilities when they are exposed to parabolic motion content.